Study on char reinforcing of different inorganic fillers for expandable fire resistance silicone rubber. Issue 28 (8th March 2021) - Yu, Jiangjiang; Hong, Ling; Qu, Linlin
Abstract: Sodium silicate monohydrate (NSH), glass frits (GF) and aluminum hydroxide (ATH) were incorporated into room temperature vulcanized (RTV) silicone rubber (SR) as char reinforcing materials to improve the fire resistance of intumescent flame retardant silicone rubber. SR composites containing only intumescent flame retardant such as phosphorus nitrogen composite flame retardant (NH2 ‐C) and expandable graphite (EG) were used as comparison samples. Limiting oxygen index (LOI) test, vertical burning test (UL‐94), flame resistance test, scanning electron microscopy (SEM) and X‐ray diffraction spectroscopy tests, as well as volume variation and compression strength of char residues were used to discuss the effects of the above‐mentioned fillers on the fire resistance, char residue strength and char integrity of SR composites. The results showed that SR composite filled with only intumescent flame retardants EG and NH2 ‐C had excellent flame retardancy. After adding ATH, the char residue was relatively dense and had good compressive strength, but its thermal insulation performance was reduced. GF or NSH reduced the flame retardancy of SR composites, but it obviously played a role in binding combustion residues, forming new crystals and improving the stability of char residues. Abstract :